Formação continuada de professores da educação básica em contextos integrados: entre a universidade e a escola - Cardona, Marcia Pires (2019)
The present study aims researching the movements of a Critical Reflexive Community of Teachers so to check the methodological possibility of this organization in acting as a driving force of the collaborative processes of the teacher’s continuous formation. The research is linked to Professional Master’s Degree of Federal University of Santa Maria (UFSM) – Research Line 2 – Pedagogical and Educational Management Contexts. The option for this subject is justified by the experience of the author’s teaching in Children’s Education and as guardian in Pedagogy Course of UAB – UFSM. The general aim is understanding the elements that organize the collaborative formation processes of a critical Reflexive Community of Teachers as a driving force in the elaboration of different contexts in teaching. We draw this research through an analogy to the trees and the processes already experienced meaning that continuous formation can be understood as an organic movement alive and in constant development. To get to this understanding we refer to theoretical references contemplating the studies of Freire (1986), Gimeno Sacristán (2000), Pinazza (2013), Formosinho (2009), Pinto (2003), Mallman (2015), Segat (2016) and Cortesão (2017). The research will be developed through qualitative approach research-action type characterizing as problem maker investigation regarding demands and group actions that contribute for the continuous formation of teachers reflected in the school environment. The subjects of the investigation are the participant teachers of the group of Research Teaching, Infancy and Formation (DOCINFOCA/UFSM) in public and private schools at the city of SM – RS. The product of this research will be the organization and implementation of an Extended Project of Continuous Formation proposed through “moodle”, aiming to make possible studies and reflections on continuous graduation in context, involving the teachers of the net as well as those coming from Educational Courses.